OCT Angiography in the Diagnosis of Small Choroidal Tumors - Elena Myakoshina (Journal of Global Pharma Technology, 2018)
Introduction small choroidal melanoma is a malignant tumor with early metastasis. It is similar to delimited hemangioma, choroidal nevus and choroidal metastatic carcinoma. The main sign of tumors is their own vessels diagnosed with various methods. However, optical coherence tomography angiography (OCT-A) was not used before. Purpose of this research is to study and compare the OCT-A criteria in the cases of small melanoma, delimited hemangioma, choroidal nevus and choroidal metastatic carcinoma cases. Methods in small melanoma, delimited hemangioma, choroidal nevus and choroidal metastatic carcinoma cases, there was performed a prospective and non-randomized OCT-A with a NIDEK RS-3000 Advance Optical Coherent Tomography (Japan). Results this method was used to examine 120 patients with small choroidal melanoma (41), delimited choroidal hemangioma (32), choroidal nevus (37) and choroidal metastatic carcinoma (10). Tumors thickness: degree – 2.2 ± 0.3 mm, diameter – 8.1 ± 0.6 mm. In the case of small melanoma, vascular network is loop-shaped with elements interweaving under the retinal vessels. In the case of delimited hemangioma, we have pictured a rich tree-like vasculature organized as a large trunk with branches (20) and diffuse scattered one organized as many small convoluted vascular branches (12). In the case of choroidal nevus, we have detected a capillary-free zone with dilated choriocapillarises around the periphery. In the case of choroidal metastatic carcinoma, vascular system was organized as a web of small vessels. Conclusion OCT-A allows diagnosing the features of angioarchitectonics in small melanoma, delimited hemangioma, choroidal nevus and choroidal metastatic carcinoma cases to provide further adequate eye-preserving treatment.Keywords: Small Choroidal Melanoma, Choroidal Delimited Hemangioma, Choroidal Nevus, Choroidal Metastatic Carcinoma, Optical Coherence Tomography Angiography (Oct-A).